PENGARUH STRATEGI BISNIS, KARAKTER EKSEKUTIF, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Natalia Kristiwi Windyasari; Fadjar Harimurti; Suharno Suharno (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the influence of business strategy, executive character and company size on Tax Avoidance. This study studies food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. The data source used is secondary data. The study population was 19 companies by analyzing financial statements from 2014-2017 accessed by the IDX website, www.idx.co.id. The sampling technique uses purposive sampling technique with a sample of 10 companies. The data analysis tool uses Multiple Linear Regression. Based on the results of the study, the business strategy does not affect Tax Avoidance. The executive character variable does not affect Tax Avoidance. Company size variables have a significant positive effect on Tax Avoidance. Proobability Value F Test 0.006 < 0.05 means the selection of the right model. There is the influence of business strategy, executive character, size of the company on tax avoidance. The test results of the determination coefficient (R2) adjusted R2 is 0.229, which means that the influence of business strategy variables, executive character and firm size on tax avoidance is 22.9%.